Causative Factors of Tooth Wear among Patients Visiting a Tertiary Care Hospital in Lahore - Qudsia Iqbal, Muhammad Waseem Ullah Khan, Muhammad Sohaib Nawaz, Hamna Khawaja, Momina Akram, Hafiz Nasir Mahmood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tooth wear, or as it is also often referred to as non-carious tooth surface loss (TSL), can be described simply as ‘the pathological non-carious loss of tooth tissue’. Tooth wear is often multifactorial in nature, making clinical diagnosis difficult. Identification of the etiology is essential for the successful management of the pathology. Methods: A total of 120 patients of both male and female with tooth wear were selected from dental OPD. Patients with age group 25-65years with tooth wear in at least two teeth according to basic erosive wear examination (BEWE) were included. Questionnaire covering primary risk factors that might cause tooth wear was used Data was analyzed using SPSS version 24.0. Results: Out of the 120 tooth wear patients, 69(57%) were male and 51(43%) were females. tooth wear presented more in males as compared to females. 42.24% patients reported with habit of tea consumption and 32.5% with cold drinks. 45% males and 43.4% females had gastric reflex disease. 60.9% male patients had problem of bruxism and clenching. Conclusion: This study reported that TSL has a multifactorial etiology. Parafunction, gastro esophageal reflux disease (GORD) and consumption of carbonated drinks were the most commonly observed causative factors. Keywords: Tooth wear, Erosion, Abrasion, Attrition, Causative factor